2021
DOI: 10.21037/atm-20-3767
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and key pathways in atrial fibrillation associated with mitral valve disease identified by multi-omics study

Abstract: Background: Mitral valve disease (MVD)-associated atrial fibrillation (AF) is one of the most common arrhythmias with an increased risk of thromboembolic events. This study aimed to identify the molecular mechanisms and possible biomarkers for chronic AF in MVD by using multi-omics methods.Methods: This prospective study enrolled patients with MVD (n=100) undergoing mitral valve replacement surgery. The patients were allocated into chronic AF and sinus rhythm (SR) groups. Plasma samples were collected preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…In many cases, the patients were volunteers, so there may be a possible selection and observation bias. Further validation of markers in larger independent data sets are needed [13][14][15][16][17], especially in human studies, where highlighted plasma biomarkers may not reflect changes in heart tissue with enough confidence to be used in patient stratification yet [13,15,16,18] and further research in this field is needed to define sensitive predictive or diagnostic biomarkers for AF. Besides that, proposed metabolic biomarkers were analyzed only in certain metabolic pathways, although the participation in more complex processes is well known [13,14,16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In many cases, the patients were volunteers, so there may be a possible selection and observation bias. Further validation of markers in larger independent data sets are needed [13][14][15][16][17], especially in human studies, where highlighted plasma biomarkers may not reflect changes in heart tissue with enough confidence to be used in patient stratification yet [13,15,16,18] and further research in this field is needed to define sensitive predictive or diagnostic biomarkers for AF. Besides that, proposed metabolic biomarkers were analyzed only in certain metabolic pathways, although the participation in more complex processes is well known [13,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…After the bioinformatic analysis, it was observed that some of the molecules found as possible biomarkers have not yet been described, thus their clinical impact is unknown [18]. Likewise, it is possible that there are still undiscovered markers that can be used for patient stratification [6,[13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations